Determination Of Nursing Students' Time Management Skills - Ceylan Bıçkıcı; Serap Torun (Association of Nurse Managers, 2021)
INTRODUCTION: This study was carried out to determine the time management skills of nursing students. METHODS: The population of the descriptive study consisted of 914 students studying at the faculty of health sciences nursing department of a public university. All students who were willing to participate were included in the study and 593 students formed the sample of the study. In the study, the personal information form prepared by the researcher and the 'Time Management Inventory' developed by Britton and Tesser in 1991 in a five-point Likert style were used. Mann -Whitney U, Kruskal -Wallis, Bonferroni tests and post-hoc analysis were used to evaluate the data. RESULTS: It was found that the time management scale scores of the students participating in the study were high and there were statistically significant relationships between the variables of gender, age, working status, class level, accommodation and economic status and scale dimensions (p<0.05). In addition, it was found that there were no statistically significant differences between the variables of the high school type in which the students studied, their place of residence, family types, and the scale scores. DISCUSSION AND CONCLUSION: As a result of the study, it was concluded that students aged 21 and over, studying in their last year of education and living with their families had managed their time better. It has been determined that female students avoided spending extra time more than male students. In addition, it was found that nursing students' time management skills are at a high level.